The Relation Between Lower Spinal Congenitalanomalies and Chronic Low Back Pain - Mirza, Raoof. R. (Sulaimani Journal for Pure and Applied Sciences, 2001)
To find out the relation of lower spinal congenital anomalies (CA) to chronic low back pain (LBP "(back pain for more than 3 months': One hundred patients with chronic LBP in whom the cause had not been identified were studied, found that 30 patients (30%) had some kind of CA in their lower spines, while in the other 70 (70%) there were no any identified CA. At the same time 66 normal people who had not suffered from back pain studied on the same standards, found that 19 (28.87%) of them had some kind of CA in their lower spines, while in the rest 47 (71.21%) there were not any evident CA. These figures give a conclusion that there is no definite relation between lower spinal CA and chronic LBP (p-value>0.8).
Keywords: Low back pain LBP and congenital anomalies CA